Cumulative prognostic power of laminin genes in colorectal cancer - Vladimir V. Galatenko; Diana V. Maltseva; Alexey V. Galatenko; Sergey Rodin; Alexander G. Tonevitsky (BMC, 2018)
Abstract Background Laminins are a major family of extracellular matrix proteins and the main component of basement membranes. Laminins are involved in many if not all stages of cancer progression, and expression of laminin genes has prognostic value in various types of cancer, including colorectal. Only single laminin genes or components of a single laminin trimer with significant differential expression have been regarded as potential biomarkers to date. Results Here we compared prognostic power of classifiers constructed from sets of laminin genes with that of any single laminin gene. The analysis showed that cumulative prognostic power of sets of laminin genes was higher and was achieved already with pairs and triples of the genes. Interestingly, components of the pairs and the triples did not belong to any known laminin trimer, but, taken together with the gene weights, suggested higher LAMA4/LAMA5 expression ratio in patients with poor prognosis. Conclusions Analysis of the laminin expression profile rather than expression of the single genes or components of laminin trimers is useful for colorectal cancer prognosis in patients. High LAMA4/LAMA5 ratio is associated with increased permeability of basement membranes suggesting that basement membranes produced by colorectal tumors might be an important hindrance to their own dissemination in patients.